2017
DOI: 10.3952/physics.v57i2.3514
|View full text |Cite
|
Sign up to set email alerts
|

The crystalline structure of SrRuO3: Application of hybrid scheme to the density functionals revised for solids

Abstract: The crystalline structure of ground-state orthorhombic SrRuO 3 is reproduced by applying the hybrid density functional theory scheme to the functionals based on the revised generalized-gradient approximations for solidstate calculations. The amount of Hartree-Fock (HF) exchange energy is varied in the range of 5-20% in order to systematically ascertain the optimum value of HF mixing which in turn ensures the best correspondence to the experimental measurements. Such investigation allows one to expand the set o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…u.) other changes in the crystalline structure [34]. The energy value 1.6 meV can be related to the localized states and the lowest value 0.007 meV is most likely due to the abovementioned two-line intensity change.…”
Section: Resultsmentioning
confidence: 92%
“…u.) other changes in the crystalline structure [34]. The energy value 1.6 meV can be related to the localized states and the lowest value 0.007 meV is most likely due to the abovementioned two-line intensity change.…”
Section: Resultsmentioning
confidence: 92%
“…As it was noticed by Rondinelli et al, 16 the measurement of oxygen positions in thin films, required to identify the octahedral behavior, is a truly complicated task due to the limited volume of the samples, the presence of a thick substrate, and a weak scattering from oxygen atoms. Having that in mind, in a recent study, 17 we have performed first-principles calculations which revealed that, within the hybrid density functional theory (DFT) framework, tensile strained SrRuO 3 indeed prefers the Cmcm rather than the I4/mmm lattice, as the difference in total energy is 40 meV per formula unit (f.u.) in favor of the former symmetry.…”
Section: ■ Introductionmentioning
confidence: 99%